Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Wahana Semesta Citra Banyuasin - Riri Hanifa; Randu Rendra Beligi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of organizational culture on employee performance at PT. Wahana Semesta Citra Banyuasin. The analytical method used is data analysis method (validation test and reliability test), normality test, simple regression analysis, and coefficient of determination analysis/R². The results showed that the validation test of organizational culture variables and the validation test of performance variables at the critical value for the sample at a significant level of 5% was 0.304, indicating that all questions were valid, because the value was > 0.304. Thus the measuring instrument used in this study is suitable for measuring organizational culture variables and performance variables. The reliability test shows that all variables are reliable, because Cronbach's Alpha > 0.60. The results of the regression analysis are Y = 4,564 + 0,957 X. The meaning of the equation: (1) Constant (β) is 4,564, meaning that without the Organizational Culture Variable (X), the magnitude of the Performance Variable (Y) is 4,564. (2) Organizational culture variable (X1) 0.957, has a positive regression coefficient. These results indicate that an increase in the organizational culture variable (X) will be accompanied by an increase in the performance variable (Y). Based on the data normality test, it is known that all data are normally distributed. It is known from the value of Asym. Sig (2-tailed) all variables, namely organizational culture and performance variables, are greater than 0.05 or 5%. From the results of the coefficient of determination (R²) test, the R Square value is 0.734 or 73.4%. This shows that the performance of employees at PT. Wahana Semesta Citra Banyuasin can be explained by 73.4% by the independent variable, namely organizational culture. while the remaining 26.6% is influenced by other factors. The value of the coefficient of determination of the organizational culture variable is 0.734, close to one (1) meaning that the ability of the organizational culture variable to cause the existence of the performance variable is getting stronger. Based on the value of the t-test for the Organizational Culture Variable of 10,898 with a significant level of 0.000. From the significant value of the organizational culture variable, which is smaller than the value of Alpha = 0.05, it can be said that the supervision variable has a very significant effect on the Performance Variable.